MICE MARKETING MIX ON PRIME PLAZA HOTEL SANUR - I Wayan Agus Pradnya Setiawan; I Ketut Astawa; I Gusti Made Wendri; Made Ruki (Politeknik Negeri Bali, 2018)
Customer satisfaction is the comparison between performances expected by the customer compared to actual performance in the field. When the actual performance is higher than the customer expectations then the customer feel satisfied and vice versa. In the case of service companies, customer satisfaction is one of the important factors in creating a good business climate. In this case, the researcher would like to research the marketing mix done at Prime Plaza Hotel Sanur to see how the performance comparison and the importance of marketing mix elements at Prime Plaza Hotel Sanur will be calculated using Importance Performance Analysis (IPA) method. From 16 indicators, on average everything has met the expectations of customers.